Is there a growing social acceptance of earnings inequalities in Poland? - Kumor, Paweł (Annales. Etyka w Życiu Gospodarczym, 2019)
In our studies, we deal with the estimating of the optimal ranges of earnings – the optimal Gini indexes which are favourable to the maximisation of GDP growth in Poland. We suspect that the optimal Gini coefficients expressing the whole of society’s acceptance of earnings inequalities can increase. In the article, we formulated a hypothesis on society’s habituation to increasing earnings disparities. We verified the hypothesis on the basis of the model of economic growth using data from 1970 to 2007. We carried out econometric studies in two stages. In the first stage, we estimated the optimal Gini coefficients for short subsequent sub-periods. In the second stage, we studied the character of changes in the optimal Gini coefficients. In the studies, we proved the hypothesis on society’s habituation to increasing earnings disparities. The optimal Gini coefficients increase along with the increase of differences in earnings and the increase of the economic level per capita. The growth of the optimal Gini coefficients may be slowed down.